When AI Joins the Counseling Room: Students’ Trust, Disclosure, and Therapeutic Alliance in AI-Assisted Counseling - Neni Noviza (Bulletin of Counseling and Psychotherapy, 2026)
The growing use of artificial intelligence in psychological support has positioned AI-assisted counseling as a promising approach to expand access, reduce stigma, and provide immediate support for students. However, counseling is not merely a technical process; it is fundamentally relational, requiring trust, self-disclosure, and therapeutic alliance to function effectively. Despite increasing interest in AI-based mental health services, limited research has specifically examined how these relational dimensions interact in student populations. This study aimed to investigate students’ trust, disclosure, and therapeutic alliance in AI-assisted counseling, as well as the relationships among these variables. A cross-sectional field survey was conducted with 1,284 undergraduate students from 12 universities across Indonesia. Data were collected using structured Likert-scale instruments and analyzed through descriptive statistics, Pearson correlation, and multiple regression. The findings showed that students reported moderately positive levels of trust, disclosure, and therapeutic alliance. Trust was positively associated with disclosure and therapeutic alliance, while trust and disclosure jointly predicted therapeutic alliance. These findings suggest that AI-assisted counseling may serve as a valuable initial support tool, but its effectiveness depends heavily on relational acceptance.